Surgical Treatment of Severe Mitral Insufficiency in Patients with Mitral Valve Prolapse - S. I. Mokhnatyi; O. M. Dovgan (Ukrainian Journal of Cardiovascular Surgery, 2019)
In this paper we represent the experience of the UCCC of the Ministry of Health of Ukraine in the surgical treatment of patients with mitral insufficiency caused by the prolapse of the mitral valve (MV) cusps.The aim. To analyze our own experience in reconstructive interventions on MV in patients with mitral valve prolapse.Materials and methods. From January 2011 to December 2017, 146 patients with severe mitral insufficiency underwent surgical interventions on the basis of the UCCC due to the prolapse of the mitral valve cusps.Results. MV repair was final in 144 (98.6 %) patients. At the time of discharge, 33 (23.9 %) patients had no residual MV insufficiency. Minimum (trivial) MV insufficiency was found in 97 (66.4 %) patients, mild MV insufficiency in 15 (10.3 %), and moderate in 1 (0.7 %) patient. There were no patients with severe MV insufficiency at the time of discharge. Therefore, mitral valve repair was successful in 145 (99.3 %) patients. Freedom from moderate and severe MV insufficiency in the remote postoperative period decreased and amounted to 95.4 %. We analyzed 8 patients who had reoperation or showed progression of residual mitral insufficiency. All of them had satisfactory result at the time of discharge from the hospital, but had unsatisfactory result at the follow-up. The reason for the unsatisfactory result was the use of artificial chords and suture annuloplication.Conclusion. Successful mitral valve repair is possible in most cases of severe mitral valve regurgitation caused by MV prolapse. A good immediate postoperative result does not mean long-term valve competency. Suture annuloplasty is a strong risk factor for the progression of MV insufficiency in the postoperative period. Resection of the posterior cusp in complex MV repair has positive impact on the long-term prognosis.